Transformation of Melinjo seed micropowders into nanopowders enhances extractability of phenolic compounds and tyrosinase inhibitory activity - Vienna Saraswaty,; Suparta, Ni Wayan Wulan Prawerti; Setiyanto, Henry; Rachmawati, Heni; Adnyana, I Ketut (Penerbit Universiti Kebangsaan Malaysia, 2019)
Melinjo (Gnetum gnemon L.) seed powder extract exhibited antioxidant and tyrosinase inhibitory activity, thus showing potential as a dietary supplement or nutraceutical to prevent aging or hyperpigmentation. Previously, we found that particle size plays important role in extraction of bioactive compounds and influences their bioactivity. Thus, it is important to determine a certain particle size for the extraction process. In this study, we investigated the effects of transformation of melinjo seed micropowders into nanopowders by nanomilling using a high-energy ball mill (shaker mill). The effects of melinjo seed powders particle size on its physicochemical characteristics, extraction efficiency and release of phenolic compounds, as well as tyrosinase inhibitory activity were observed. The nanomilling successfully transformed melinjo seed micropowders into nanopowders within 90 min of milling. Particle size analysis showed that melinjo seed nanopowders were produced with a mean particle diameter of ~675 nm (PI 0.270). Scanning electron microscope (SEM) images of the melinjo seed nanopowders obviously showed a smaller particle size, a smooth surface, amorphous shapes and irregular edges. The melinjo seed nanopowders at mean particle diameter of ~675 nm exhibited the highest extraction yield and phenolic compounds release. As a consequence, the tyrosinase inhibitory activity of the melinjo seed nanopowders was 4.5 times higher than that of the melinjo seed micropowders. Based on the results obtained in this study, transformation of melinjo seed micropowders into nanopowders is very promising for improving the efficacy of melinjo seed as tyrosinase inhibitor.